Food insecurity and adverse pregnancy outcomes among rural Malawian women. Issue 2 (17th February 2021) - Hood, Robert B.; Norris, Alison H.; Huber‐Krum, Sarah; Garver, Sarah; Chapotera, Gertrude; Turner, Abigail N.
Abstract: Objective: To investigate whether food insecurity is associated with adverse pregnancy outcomes such as miscarriage, stillbirth, and neonatal mortality among women in rural Malawi. Methods: We analyzed data from the baseline (July 2014 to February 2015) and follow‐up (January 2018 to May 2018) waves of a longitudinal study of reproductive‐age women in rural Malawi. We sampled women from villages from the catchment area of a community hospital in rural Lilongwe district of Malawi using stratified cluster sampling. We classified women as food secure or insecure at baseline. Using unadjusted and adjusted log‐binomial models, we used baseline data to examine the cross‐sectional association between food insecurity and ever experiencing an adverse pregnancy outcome. We used baseline and follow‐up data to assess the longitudinal association between food insecurity and experiencing a new adverse pregnancy outcome during follow‐up. In a subgroup analysis, we repeated the longitudinal analysis after restricting the sample to women who had no adverse pregnancy outcomes at baseline. Results: We observed no significant cross‐sectional association between baseline food insecurity and ever experiencing an adverse pregnancy outcome (adjusted prevalence ratio: 1.09; 95% confidence interval [CI]: 0.78–1.53). Baseline food insecurity was not associated with experiencing a new adverse pregnancy outcome during follow‐up (adjusted risk ratio [aRR]: 1.14, 95% CI: 0.60–2.20) or in the subgroup analysis (aRR: 1.52, 95% CI: 0.78–2.96). Conclusions: While food insecurity is a critical issue, in this cohort of rural Malawian women, food insecurity was not associated with adverse pregnancy outcomes. Abstract : While food insecurity was high at baseline, it was not associated with adverse pregnancy outcomes among this cohort of rural Malawian women.